2010
DOI: 10.1016/j.nmd.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of gait in Golden Retriever Muscular Dystrophy

Abstract: The goal of this study was to quantify the two-dimensional kinematics of pathologic gait during overground walking at a self-selected speed at the stifle (knee) and hock (ankle) joints in six Golden Retriever Muscular Dystrophy (GRMD) dogs and six carrier littermates (controls). We found that GRMD dogs walked significantly slower than controls (p < 0.01). At the stifle joint, both groups displayed similar ROM (range of motion), but compared to controls, GRMD dogs walked with the stifle joint relatively more ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…The presence of an orthopaedic/neurological condition also revealed to be a factor of decrease in the mobility of dogs. Similar decreases of mobility have been reported in other studies (POY et al, 2000;MARSOLAIS et al, 2003;COOK, 2010;MARSH et al, 2010;RAGETLY et al, 2010;SANCHEZ-BUSTINDUY et al, 2010;). The absence of floor and ceiling effects on this DMS suggests favourable sensitivity of this scale for evaluation of additional validity studies (INNES & BARR, 1998;TERWEE et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…The presence of an orthopaedic/neurological condition also revealed to be a factor of decrease in the mobility of dogs. Similar decreases of mobility have been reported in other studies (POY et al, 2000;MARSOLAIS et al, 2003;COOK, 2010;MARSH et al, 2010;RAGETLY et al, 2010;SANCHEZ-BUSTINDUY et al, 2010;). The absence of floor and ceiling effects on this DMS suggests favourable sensitivity of this scale for evaluation of additional validity studies (INNES & BARR, 1998;TERWEE et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…The body will compensate by increasing or decreasing the ROM in the cervicothoracic and thoracolumbar vertebral regions (Eward et al, 2003;Hogy et al, 2013;Marsh et al, 2010;Miqueleto et al, 2013). Our study found in the trotting gait of dogs affected with bilateral PL that bilateral PL was the cause of the increase in the ROM of the carpal joint, while unilateral PL was found to be the cause of a decrease in the ROM of the shoulder, in comparison with unaffected dogs.…”
Section: Discussionsupporting
confidence: 43%
“…Joint motion plays an important role in maintaining the functions of the joints as many tissues are affected in the ROM, for example articular cartilage, joint capsule, tendon, ligament, bone and muscle. Various conditions have been reported as limiting the ROM: Septic arthritis, osteoarthritis, joint luxation, bone and articular fracture, ligament/tendon rupture and muscle contraction (Marsh et al, 2010;Miqueleto et al, 2013). Treatments of the disorders of those tissues are aimed at bringing about the re-function of the joints, thus returning the ROM to normal as a result of which the dog can walk, trot, canter, or gallop as normal.…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard methods used for clinical assessment of DMD patients, such as the 6-minute walk test, 81 were shown to be difficult to set up in the canine model. 82 Also, the functional quantitative methods using kinematics and accelerometry that were recently published 82,83 enable the comparison of the gait between GRMD dogs and healthy ones. Further investigations will be necessary to determine whether they could represent reliable tools to assess the efficacy of MuStem cell therapy in GRMD dogs.…”
Section: Discussionmentioning
confidence: 99%